Biological Evaluation of Some Novel Sulphur Substituted Chalcones as New Scaffold: Pharmaceutical Science-Pharmaceutical chemistry - Joseph, Mr. Mejo; Alaxander, Dr.S.; Banurekha, Dr. J.; Anandkumar, Dr. (International Journal of Life Science and Pharma Research, 2022)
In the past few decades, developing antifungal and anticancer agents has become essential in drug research. Cancer is one of the most challenging diseases in the world. Most reviews on chalcones suggested that substituted chalcones have numerous biological activities. This study aim includes synthesizing different Sulphur containing chalcones in the presence of para-amino acetophenone linked to various aldehydes in the presence of aqueous alcoholic alkali. The structural analysis of synthesized compounds was also carried out by IR, 1HNMR 13CNMR and MASS spectra. The docking study was performed by Biovia discovery studio 20202. Invitro cytotoxic activity was carried out by human breast cancer cell line MCF-7 using MTT assay. Antifungal activity was conducted by diffusion method against Candida albicans and Aspergillus niger. Novel synthesized compounds, especially BT-IV-A, BT-IV-B, BTIV- C, BT-IV-E and BT-IV-I showed significant antifungal activity as BT-IV-H, BT-IV-E, and T-IV-F revealed excellent growth-inhibitory impact for the development of new anticancer agents.